Troponin-tropomyosin: an allosteric switch or a steric blocker? - Resetar, Andrea M.; Stephens, Jacqueline M.; Chalovich, Joseph (East Carolina University, 2002)
The interaction of myosin subfragment 1 (S1) with actin-tropomyosin-troponin (regulated actin) is highly nucleotide dependent. The binding of S1 or S1-ADP (but not S1-ATP nor N,N - -phenylenedimaleimide-modified S1-ATP) to regulated actin activates ATP hydrolysis even in the absence of Ca2 . Investigations with S1 and S1-ADP have led to the idea that some actin sites are directly blocked toward the binding of S1 either by tropomyosin or troponin. The blocked state is thought to occur only at ionic strengths greater than 50 mM. The question is whether nonactivating S1 binding is blocked under the same conditions. We show that troponin inhibits binding of the nonactivating state, N,N - -phenylenedimaleimide- S1-ATP, to actin but only when tropomyosin is absent. A lag in the rate of binding of activating S1 to actin (an indicator of the blocked state) occurs only in the presence of tropomyosin. Thus, tropomyosin inhibits binding of rigor S1 but not S1-ATP-like states. No evidence for an ionic strength-dependent change in the mechanism of regulation was observed either from measurements of the rate of activating S1 binding or from the equilibrium binding of nonactivating S1 to actin. At all conditions examined, N,N - -phenylenedimaleimide-S1-ATP bound to regulated actin in the absence of Ca2 . These results support the view of regulation in which tropomyosin movement is an allosteric switch that is modulated by activating myosin binding but that does not function solely by regulating myosin binding. Originally published Biophysical Journal, Vol. 83, No. 2, Aug 2002
Keywords: Tropomyosin; Troponin; Actin; S1; S1-ADP